Report on the world social situation 2013 - United Nations (United Nations, 2013)
The 2013 report examines key drivers of inequality that have emerged in the recent past and the impact of rising inequality. It examines trends in social, economic and spatial inequalities and assesses why inequality matters in order to propose policy solutions to this persistent problem, paying particular attention to the potential role of empowerment and participation. The report highlights inequalities within and across countries and shows the cumulative, mutually-reinforcing effects these inequalities have on the systematic lack of participation and disadvantage of some social groups and on the intergenerational transmission of poverty. It discusses the role of economic and political institutions in promoting participation and empowerment.